De Novo Assembly, Characterization and Functional Annotation of Southern Hake (Merluccius Australis) Transcriptome - Vidal-Soto, R (Frontiers Media S. A, 2016)
Southern hake (Merluccius australis) is an ecological and economically important demersal fish in Chile and Argentina. Notwithstanding, genetic resource for genetic or ecological studies on this species are scarce. Consequently, here we present transcriptome sequencing results (RNA-Seq) for spleen and liver tissues with the 454 FLX titanium platform. The de novo transcriptome assembly generated 10,314 unigenes, with an average length of 510 bp, N50 of 572 bp and 3171 annotated sequences. A specific Gadiform BLAST search, with focus on immune genes, showed 186 (56%) genes homologous to those of Atlantic cod. A total of 2302 microsatellites were detected in 1687 unigenes and 741 presented adequate flanking sequences for primer design. In total, these potential molecular markers and transcriptome characterization represent an important resource for genetic and ecological studies on southern hake. © 2016 Reyes, Gold, González and Vidal.